Pengembangan Instrumen Penilaian Keterampilan Praktikum Kimia Anorganik melalui Google Sheet - Ruslan, Zuhrah Adminira (Program Pasca Sarjana UNM, 2023)
This research is a type of R&D research that aims to develop an instrument for assessing inorganic chemistry practicum skills conducted at the Chemistry Department of Makassar State University. The research design used refers to the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results of the study include the validity, practicality, and effectiveness of the instruments developed through expert validation, the value of inorganic chemistry practicum skills, and lecturer and practicum assistant response questionnaires. The results of the instrument validation show that a valid instrument from experts obtained a value of 3.5. Practicality was obtained from the lecturer response questionnaire and practicum assistant, namely 60% of respondents gave a score of 5, which is very practical in using the instrument for assessing inorganic chemistry practicum skills through Google Sheets. The effectiveness is obtained from the descriptive analysis of the average inorganic practicum skill value of students majoring in chemistry, namely 82 (B+).